Confusing the extragalactic neutrino flux limit with a neutrino propagation limit - Barranco, Juan; Miranda, Omar G.; Moura, Celio A.; Rashba, Timur I.; Rossi-Torres, Fernando [UNESP] (Iop Publishing Ltd, 2011)
We study the possible suppression of the extragalactic neutrino flux due to a nonstandard interaction during its propagation. In particular, we study neutrino interaction with an ultra-light scalar field dark matter. It is shown that the extragalactic neutrino flux may be suppressed by such an interaction, leading to a new mechanism to reduce the ultra-high energy neutrino flux. We study both the cases of non-self-conjugate as well as self-conjugate dark matter. In the first case, the suppression is independent of the neutrino and dark matter masses. We conclude that care must be taken when explaining limits on the neutrino flux through source acceleration mechanisms only, since there could be other mechanisms for the reduction of the neutrino flux.
Keywords: dark matter theory; ultra high energy photons and neutrinos; neutrino experiments; ultra high energy cosmic rays